2018
DOI: 10.1186/s12884-018-1673-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between social capital and maternal depression: results from a follow-up study in China

Abstract: BackgroundThis study aims to investigate the association between social capital (SC) and depressive symptoms among Chinese primiparas at different time-points from their late pregnancy to postpartum.MethodsA total of 450 primiparas were recruited for the current study. The assessments were conducted at three different time-points: T1 – while the participants were recruited at their 30–36 weeks of pregnancy in the antenatal clinic in the maternity hospital in Zhejiang, China; T2 – at their 2nd or 3rd days in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
6
10
1
Order By: Relevance
“…Tension among generations has been described as a primary source of mental health problems in the perinatal period (Xiong et al, 2018). The cross-generational conflicts could be a contributing factor to the high rates of "unstable mood," which are reported by 50%-75% of first-time mothers in China between the first trimester of pregnancy and 6 months postpartum (Zhou et al, 2018). These results are similar to data from other Asian countries, such as South Korea (Kim et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Tension among generations has been described as a primary source of mental health problems in the perinatal period (Xiong et al, 2018). The cross-generational conflicts could be a contributing factor to the high rates of "unstable mood," which are reported by 50%-75% of first-time mothers in China between the first trimester of pregnancy and 6 months postpartum (Zhou et al, 2018). These results are similar to data from other Asian countries, such as South Korea (Kim et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…In several studies, social support was negatively correlated with depression among Chinese primiparae (Huang et al, 2019;Kim et al, 2013;Zhou et al, 2018). Perceived social support and conflicts among social support providers were major contributors to stress associated with postpartum depression in previous studies in China (Tang et al, 2016;Xiong et al, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Pregnant women were late in checking their pregnancies due to a lack of information about pregnancy care (Desta et al, 2019). This is in line with Zhou et al (2018) that information about antenatal care affected pregnancy care management and reduced maternal anxiety. 5.…”
Section: The Effect Of Maternal Attitude Onsupporting
confidence: 82%
“…A cross-sectional study conducted by Forsman et al [ 20 ] also found that low levels of trust were associated with depressive symptoms among the Swedish and Finnish populations. In China, Zhou et al [ 21 ] reported a negative association between depressive symptoms and social trust among primiparas. This observation was in line with Cao et al’s [ 22 ] finding that level of trust was inversely correlated with depression in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%